Systematic literature review: development of augmented reality-based e-lkpd to improve students' creative thinking skills and learning interest in mathematics - Wardhani, Riska Ayu; Thoyibah, Thoyibah; Marhaeni, Nafida Hetty (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This research is a Systematic Literature Review (SLR) study that aims to identify and analyze the development of Augmented Reality (AR)-based electronic Student Worksheets (e-LKPD) in enhancing students’ creative thinking skills and interest in learning mathematics. The SLR method was employed to compile a synthesis of 15 peer-reviewed scientific articles published between 2018 and 2025. The articles were obtained through systematic searches using tailored keywords on academic databases such as Google Scholar and Semantic Scholar. The findings from the review indicate that AR-based e-LKPD has a significant positive impact on improving both students’ creative thinking and their motivation to learn mathematics. AR technology has been shown to effectively deliver learning content in a more visual, interactive, and contextual format, which enhances students’ active participation in the learning process. Through 3D visualization and immersive, real-world-like learning experiences, students become more interested and engaged, and are motivated to explore mathematical concepts independently. These findings suggest that AR-based interactive learning media can serve as an innovative solution to meet the demands of 21st-century education, particularly in STEM-related fields. This study provides a strong theoretical foundation for educators, instructional designers, and media developers in integrating AR into mathematics education. It underscores the importance of combining pedagogy and technology to create engaging, meaningful, and student-centered learning experiences that foster creativity and deeper understanding.